2019
DOI: 10.1088/1757-899x/571/1/012093
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Study Biological Activity of New Para-methoxy Benzene Sulfonamide Derivatives and some Amino Acid

Abstract: The synthesis of para-methoxy sulphonamides [3a-3G] was obtained by reacting p-methoxy benzene sulphonyl chloride with primary amine functionalities of amine group [1a-1G] in alkaline medium at temperature below 0°C, structures of all Newly synthesized compound were analysed by FT-IR, H and CNMR spectroscopy, Anti bacterial of the titled compounds were screened and the compounds exhibited potent anti bacterial properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…From 1950s till the present day, the synthesis of more potent high-profile sulpha drugs is still in progress. These include the antibacterial agent, sulphathiazole 12 [16], the carbonic anhydrase inhibitor, acetazolamide 13 [17] [18] which has been in use clinically for more than 45 years, the diuretic agent, Furosemide 14 [19] the hypoglycemic agent glibenclamide 15 [20], the anticancer sulphonamide, indisulam 16 [21], the aspartic HIV protease inhibitor amprenavir 17 [22] used for AIDS and HIV infection management and the metalloprotease (MMP) inhibitors 18 of the sulphonyl amino acid hydroxamate [23] just to mention but a few (Figure 5).…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…From 1950s till the present day, the synthesis of more potent high-profile sulpha drugs is still in progress. These include the antibacterial agent, sulphathiazole 12 [16], the carbonic anhydrase inhibitor, acetazolamide 13 [17] [18] which has been in use clinically for more than 45 years, the diuretic agent, Furosemide 14 [19] the hypoglycemic agent glibenclamide 15 [20], the anticancer sulphonamide, indisulam 16 [21], the aspartic HIV protease inhibitor amprenavir 17 [22] used for AIDS and HIV infection management and the metalloprotease (MMP) inhibitors 18 of the sulphonyl amino acid hydroxamate [23] just to mention but a few (Figure 5).…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…From 1950s till the present day, more potent high-profile sulpha drugs are being produced. These include the antibacterial agent, sulphathiazole 12 [16], the carbonic anhydrase inhibitor, acetazolamide 13 [17,18] which has been in use clinically for more than 45 years, the diuretic agent, Furosemide 14 [19] the hypoglycemic agent glibenclamide 15 [20], the anticancer sulphonamide, indisulam 16 [21], the aspartic HIV protease inhibitor amprenavir 17 [22] used for AIDS and HIV infection management and the metalloprotease (MMP) inhibitors 18 of the sulphonyl amino acid hydroxamate [23] just to mention but a few (Figure 5) Studies have shown that the presence of folate (folic acid) 22 is very vital in the manufacture of nucleic acids present in the cell wall of bacteria [24] while its absence renders the cells inactive and prevent DNA synthesis. This can be seen when sulphonamide 8 reacts with dihydropteridine diphosphate 19 to form dihydropteroic sulphonamide 23 in the path way B (scheme 1) [25] which hinders further reaction for the formation of folic acid.…”
Section: Introductionmentioning
confidence: 99%